PREVENTIVE ACTIVITY OF TEACHER AS A MEANS PREVENTION OF ASOCIAL BEHAVIOR JUNIOR SCHOOLCHILDREN (Pedagogy of Higher and Secondary Education, 2022)
The article is dedicated pecularietes of pedagogical support and priventive activity to avoid unsocial tanager's behavior.